Positive Modulatory Interactions of NMDA Receptor GluN1/2B Ligand Binding Domains Attenuate Antagonists Activity - Bledsoe, Douglas; Tamer, Ceyhun; Mesic, Ivana; Madry, Christian; Klein, Bradley G.; Laube, Bodo; Costa, Blaise M. (Frontiers in Pharmacology, 2017)
N-methyl D-aspartate receptors (NMDAR) play crucial role in normal brain function and pathogenesis of neurodegenerative and psychiatric disorders. Functional tetra-heteromeric NMDAR contains two obligatory GluN1 subunits and two identical or different non-GluN1 subunits that include six different gene products; four GluN2 (A-D) and two GluN3 (A-B) subunits. The heterogeneity of subunit combination facilities the distinct function of NMDARs. All GluN subunits contain an extracellular N-terminal Domain (NTD) and ligand binding domain (LBD), transmembrane domain (TMD) and an intracellular C-terminal domain (CTD). Interaction between the GluN1 and co-assembling GluN2/3 subunits through the LBD has been proven crucial for defining receptor deactivation mechanisms that are unique for each combination of NMDAR. Modulating the LBD interactions has great therapeutic potential. In the present work, by amino acid point mutations and electrophysiology techniques, we have studied the role of LBD interactions in determining the effect of well-characterized pharmacological agents including agonists, competitive antagonists, and allosteric modulators. The results reveal that agonists (glycine and glutamate) potency was altered based on mutant amino acid sidechain chemistry and/or mutation site. Most antagonists inhibited mutant receptors with higher potency; interestingly, clinically used NMDAR channel blocker memantine was about three fold more potent on mutated receptors (N521A, N521D & K531A) than wild type receptors. These results provide novel insights on the clinical pharmacology of memantine, which is used for the treatment of mild to moderate Alzheimer’s disease. In addition, these findings demonstrate the central role of LBD interactions that can be exploited to develop novel NMDAR based therapeutics.